Speaking to Devices: Can we Use Google Assistant to Foster Students' Speaking Skills? - Hadi, Muhamad Sofian; Junor, Raisya Syafira (Universitas Pendidikan Mandalika, 2022)
Teaching speaking skills needs appropriate medias to facilitate students to practice and imitate English speakers accurately. One of applications that can help students learn speaking skills is Google assistant application. This study aims to foster students’ speaking skills through the use of the Google Assistant application on devices. This study employed the application to provide students with various speaking materials. This study was designed in an experimental study which was to know whether the use of Google Assistant helps students in fostering their speaking skills or not. This study uses pre-experimental as the research design. The study involved 31 participants of eleventh-grade students in DUA MEI Senior High School, Tangerang Selatan. The data was collected from pre-test and post-test. Based on the analysis, the results show that the t-cal value (12.436) was higher than the t-table (2.042), at the 5% significant level. It indicated that the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted. Based on the results of the t-test calculation, this study can be concluded that Google Assistant is an effective medium to facilitate students' fostering their speaking skills.